Edukasi Self Care Pasca Vaksinasi Pada Kelompok Lansia Di Taba Penanjung Bengkulu Tengah - Encik Putri Ema Kemala; Tuti Anggriani Utama; Desi Susilawati (Universsitas Mitra Indonesia, 2021)
AbstractThe government's policy of carrying out the Covid-19 vaccination in January 2021 is still getting doubts in the hearts of the people. The level of acceptance varies in each province, this is motivated by knowledge, personal experience, culture, religious beliefs, community attitudes. The problem with Taba teret sub-district partners is that 80% of vaccinations have not been achieved and many people do not want to take vaccinations at the puskesmas or other health facilities, this is due to concerns and lack of public knowledge about self-care after the covid-19 vaccination. Based on this phenomenon, we from the community service team of the D3 Nursing Study Program, Faculty of Mathematics and Natural Sciences, Bengkulu University, took part in educating the public about post-vaccination self-efficacy in the Elderly Group in Taba Penanjung Bengkulu. The community service method uses a mentoring and socialization approach by means of lectures, questions and answers, discussions which are attended by 12 people. The results of this community assessment for the level of public knowledge before and after education in the category were obtained from 12 participants, 67% answered incorrectly on the question